Predicting the right mechanism for hypervalent iodine reagents by applying two types of hypervalent twist models: apical twist and equatorial twist. Issue 11 (12th March 2021) - Sun, Tian-Yu; Chen, Kai; Lin, Qihui; You, Tingting; Yin, Penggang
Abstract : Since hypervalent twist followed by reductive elimination is a general reaction pattern for hypervalent iodine reagents, mechanistic studies about the hypervalent twist step could provide significant guidance for experiments. Abstract : Since hypervalent twist followed by reductive elimination is a general reaction pattern for hypervalent iodine reagents, mechanistic studies about the hypervalent twist step could provide significant guidance for experiments. Previous studies have shown that there are two types of hypervalent twist models, i.e. apical twist and equatorial twist. We applied both hypervalent twist models to explain the isomerization mechanism of two important electrophilic trifluoromethylating reagents, Togni I and Togni II. Up to now, there are less detailed studies about the different hypervalent twist modes between both reagents. Here, we successfully identified Togni II's isomerization pathway via equatorial twist, and suggested that different hypervalent twist models should be considered to predict the right mechanisms of reactions with hypervalent iodine reagents participating. This study will also be helpful to design new Togni type reagents with higher intrinsic reactivity and stability by avoiding the formation of acyclic by-products.